Pengembangan Video Animasi pada Materi Sistem Pernapasan Kelas VIII - Tari Saleva; Sepriyaningsih Sepriyaningsih; Linna Fitriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine and describe the validity, practicality, and effectiveness of students’ learning outcomes through the development of an animated video on the topic of the human respiratory system for Grade VIII students at SMP Negeri 9 Lubuklinggau. This research employed a research and development (R&D) method using the ADDIE model, with a trial conducted on 27 Grade VIII students of SMP Negeri 9 Lubuklinggau. The results showed that: (1) the material expert validation obtained a percentage score of 56%, the language expert validation obtained 57%, and the media expert validation obtained 68%; (2) the practicality test consisted of student and teacher responses, in which the student response reached 92% and the teacher response reached 98%; and (3) students’ learning outcomes were obtained through pretest and posttest evaluations, which resulted in an N-Gain score of 0.77, categorized as high. Based on the overall results of validity, practicality, and effectiveness testing, it can be concluded that the animated video on the human respiratory system for Grade VIII students at SMP Negeri 9 Lubuklinggau meets the criteria of being valid, practical, and effective, and is therefore feasible for use in science learning, particularly on the topic of the human respiratory system. Keywords: ADDIE, Video Animasi, IPAS, Learning Media